Nanomechanical, mechanical and microstructural characterization of electron beam welded Al2219-T6 tempered aerospace grade alloy: A comprehensive study - Ghulam Hussain; Tauheed Shehbaz; Mohammed Alkahtani; Usman Abdul Khaliq; Hongyu Wei (Heliyon, 2024)
As compared to traditional fusion welding processes, electron beam welding (EBW) is known to produce structurally robust microstructures and narrow heat-affected zone (HAZ) in metals. The process becomes more significant for the tempered alloys vulnerable to heat exposure. In the present investigation, Al 2219-T6 alloy was joined using the EBW process. The microstructural, mechanical, and nanomechanical characteristics of the resulting joint were investigated. EBW resulted in a narrow HAZ (22 μm) with a 430 mm fusion zone (FZ). A dendritic structure was observed in the FZ zone, while second-phase particles were absent indicating their dissolution during welding and interesting formation of Al2Cu mixture around the dendrites. The limited content of Cu in the base metal (BM) resulted in the formation of a solid solution in the FZ, along with the presence of fine equiaxed grains in the HAZ and equiaxed dendritic grains in the FZ zone. The X-ray diffraction analysis confirmed the absence of peaks corresponding to incoherent phases in the FZ. Compared to the BM, micro-hardness measurements revealed a 12.7 % increase in the hardness in the HAZ, while a significant decrease of approximately 19 % was observed in the FZ. The joint exhibited reduced tensile strength, ultimate strength by 42.2 %, and yield strength by 47.3 % when compared to the BM. The fracture analysis indicated a ductile failure mode with the presence of microvoids. Nano-indentation tests at various loads demonstrated a decrease in the nanohardness from the BM to the HAZ and FZ regions. Atomic force microscopy (AFM) analysis revealed significant pile-ups in the FZ, indicating the occurrence of plastic deformation during the welding process. The presented findings are valuable for the joint and structure design of Al −2219T6 alloy in particular and other Al alloys in general.